Pola Asuh Pemberian Makan dan Tingkat Pendidikan Pengasuh Baduta Stunting di Wilayah Kerja Puskesmas Tete Sulawesi Tengah: Feeding Parenting Pattern and Education Level of Stunting Baby-Careers in The Working Area of Tete’s Public Health Centre, Central Sulawesi - Ririn Holifah; Adhyanti; Fahmi Hafid; Ahmad Fitrawan (Media Publikasi Cendekia Indonesia, 2023)
Background: According to the 2014 World Health Organization, the causes of child stunting include maternal nutritional status, exclusive breastfeeding, inadequate food intake and infectious diseases. In addition, other factors that affect the nutritional status of stunting are maternal characteristics of age, education, occupation or height Aims: To describe the feeding parenting pattern and the level of education of the caregivers for stunting children. Methods: This research is a cross sectional descriptive study. The research population was all stunting children in the Tete Health Center working area with a total of 154 children with a sample of 61 people. The sampling technique used proportional random sampling. Data were obtained from respondents by means of interviews using questionnaires and univariate data analysis. Results: The results of the study showed that the parenting pattern of feeding stunting children was no IMD 95.1%, not exclusive breastfeeding 63.9%, complementary feeding at the age of 6-8 months with a frequency of 2.6 times/day with a total of 0.5 servings/day. , ages 9-11 months frequency is 3 times/day with a total of 0.75 servings/day, ages 12-23 months the frequency is 3 times/day with a total of 0.75 servings/day, texture does not match 63.9%, does not vary 100 %. Parenting related to cleanliness, namely mothers do not clean their children's teeth every day 68.9%, children do not wear shoes when playing outside the house 57.4%, mothers do not clean their children's milk bottles after use (who use) 68.9%, and the level of caregiver education is SMA/MA 82.0%. Conclusion: The conclusion of the feeding parenting pattern starting from IMD, exclusive breastfeeding, MP-ASI, and the level of education of the mother in the working area of ​​the Tete Health Center, Tojo Una-Una Regency is still low, the mother's education is on average high school/MA. It is suggested that the Tete Health Center is able to improve education and innovation programs about the importance of the role of feeding parenting in children.